2010
DOI: 10.2308/jata.2010.32.1.25
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Client Advocacy in the Development of Tax Professionals’ Advice

Abstract: A primary responsibility of tax professionals is to be an advocate for their clients (AICPA 2000). Prior studies have shown mixed results on how the advocate role influences tax professionals’ decision processes and outcomes (e.g., Cloyd and Spilker 1999; Davis and Mason 2003; Barrick et al. 2004; Kahle and White 2004). In this study, we consider how advocacy may be at least partially context-specific, introduce the construct of client-specific advocacy, and thoroughly examine the influence of advocacy attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
2
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 19 publications
0
34
2
1
Order By: Relevance
“…Thus, to actualize this urge, the taxpayers can use the tax consultant's expertise and competence to carry out tax avoidance. [4] explained that for certain clients, tax consultants can consider the risks in order to use the ambiguity in tax provisions to create tax avoidance strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to actualize this urge, the taxpayers can use the tax consultant's expertise and competence to carry out tax avoidance. [4] explained that for certain clients, tax consultants can consider the risks in order to use the ambiguity in tax provisions to create tax avoidance strategies.…”
Section: Resultsmentioning
confidence: 99%
“…The dilemma of the intermediary position with different responsibilities leads to strong pressure, so it tends to place tax consultants in a difficult position to act based on the objectives expected by both parties [6,34]. Not only in Indonesia, the Australian tax authority, named Australian Tax Officers (ATO), realizes that tax consultants do not only function to provide advocacy and prepare client's tax reporting, but also provide a risk management service in order to minimize the tax payments [4,24].…”
Section: Resultsmentioning
confidence: 99%
“…Supervisory advice is provided to tax professionals in the public accounting firm environment, which has distinct hierarchical structures and clear role differentiation, and a context of accountability (Gibbins, 1984;Gibbins and Newton, 1994;Magro, 1999;Hatfield, 2001). The advice is given to meet the objectives of effectiveness, efficiency and training, but the underlying accountability could influence how the tax professional responds to the advice (Gibbins and Newton, 1994;Cloyd, 1997;Lerner and Tetlock, 1999;Bobek et al, 2010).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Notably, Duncan et al [52] found the opposite evidence showing the more risk-averse the taxpayer, the more aggressive the tax practitioner, and the more aggressive the taxpayer, the more conservative tax position recommended by the practitioner. Furthermore, Bobek et al [53] examined how the role of client advocacy influenced tax professionals' decision processes and outcomes and provided empirical results revealing that client characteristics influence tax professionals' advocacy attitudes. These findings suggest that taxpayers and tax practitioners' decisions are interdependent, and studies on their interaction dynamics could be a promising approach to find new insights into tax compliance.…”
Section: Interactions Of the Taxpayer And The Tax Practitionermentioning
confidence: 99%